National and ethnographic features of Kazakh poetry in the era of independence - Sultangalieva, О.Қ.; Yerdembekov, Б.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article describes the ideological specifics of Kazakh poetry of the period of Independence, while commenting and analyzing opinions about national values, national idea, native land, universal values, national consciousness. The problem of the patriotic spirit of the Kazakh people is that the protection of the land of our ancestors, the love of the native land is a phenomenon that permeates the national being. The article deals with the theme of the native land, national values in the works of Bauyrzhan Kurmankulov, a representative of the Kazakh poetry of the Independence period. An ideological analysis of the poet's poems "Zhympity", "Kyrykkudyk" and "Dombyra uni" from the cycle of poems "Tugan Zherde tugan zhyrlar" was carried out. The cognitive thoughts based on folk life in the poet's ambitious songs are analyzed. The poet, journalist Indira Utemis in the poems "Oyil", "Tugan germen koshtasu", "Auylga ketem" from the cycle of poems on the theme of the native land is characterized by nostalgia of the lyrical hero through tender feelings about the native land. The fiery poems of the young poetess Gulzhainar Kaldina "Makhambettin monology", "Magzhannyn monology", "Kazak – biz!", "Aybin", "Kazak degen – wass biz!", which are imbued with a critical spirit and the poem "Ake tilegi", built on the theme of education, filled with national value, are analyzed. The opinions of the famous writer Meyrkhan Akdaulet, critic Bagashar Tursynbayuly about the poet's work are given. They draw attention to the fact that the poet G.Kaldina has a high artistic level, a genuine development of events and concludes that his poems occupy an important place in our literature of the period of Independence